Odpowiedzi

2009-10-05T22:33:54+02:00
A)
A=(-3,1) B=(2,-1) C=(5,2)
lab: y=ax+b
A∈lab oraz B∈lab

1=-3a+b oraz -1=2a+b
b=1+3a stąd -1=2a + 1 +3a
-2 = 5a
a= -2/5
b=1+ 3(-2/5)
b=5/5 - 6/5
b= -1/5

lab: y=-2/5x - 1/5

lbc: y=xm + n
B∈lbc oraz C∈lbc

-1=2m +n oraz 2=5m+n
n=-1 -2m stąd 2=5m -1 -2m
3=3m
m=1
n= -1 -2 ×1
n= -3

lbc: y= x -3

lac: y = px + r
A∈lac oraz C∈lac

2=5p + r oraz 1=-3p +r
r= 2 - 5p stąd 1= -3p +2 -5p
-1=-8p
p=1/8
r= 2- 5( -1/8)
r=16/8 + 5/8
r= 21/8

lac: y= 1/8x + 21/8

b)
lh - równanie wysokości

lh: y=ax+b
lh jest prostopadła do lac stąd a × 1/8 = -1 więc a = -8

B∈lh

-1= 2 × (-8) + b
-1= -16 +b
b=15

lh: y=-8x +15
1 2 1